Sedentary behaviour and risk of all-cause, cardiovascular and cancer mortality, and incident type 2 diabetes: a systematic review and dose response meta-analysis - Patterson, Richard; McNamara, Eoin; Tainio, Marko; de Sá, Thiago Hérick; Smith, Andrea D.; Sharp, Stephen J.; Edwards, Phil; Woodcock, James; Brage, Søren; Wijndaele, Katrien (European journal of epidemiology, 2018)
Purpose: To estimate the strength and shape of the dose-response relationship between sedentary behaviour and all-cause, cardiovascular disease (CVD) and cancer mortality, and incident type 2 diabetes (T2D), adjusted for physical activity (PA). Data Sources: Pubmed, Web of Knowledge, Medline, Embase, Cochrane Library and Google Scholar (through September-2016); reference lists. Study Selection: Prospective studies reporting associations between total daily sedentary time or TV viewing time, and ≥ one outcome of interest. Data Extraction: Two independent reviewers extracted data, study quality was assessed; corresponding authors were approached where needed. Data Synthesis: Thirty-four studies (1,331,468 unique participants; good study quality) covering 8 exposure-outcome combinations were included. For total sedentary behaviour, the PA-adjusted relationship was non-linear for all-cause mortality (RR per 1 h/day: were 1.01 (1.00-1.01) ≤ 8 h/day; 1.04 (1.03-1.05) > 8 h/day of exposure), and for CVD mortality (1.01 (0.99-1.02) ≤ 6 h/day; 1.04 (1.03-1.04) > 6 h/day). The association was linear (1.01 (1.00-1.01)) with T2D and non-significant with cancer mortality. Stronger PA-adjusted associations were found for TV viewing (h/day); non-linear for all-cause mortality (1.03 (1.01-1.04) ≤ 3.5 h/day; 1.06 (1.05-1.08) > 3.5 h/day) and for CVD mortality (1.02 (0.99-1.04) ≤ 4 h/day; 1.08 (1.05-1.12) > 4 h/day). Associations with cancer mortality (1.03 (1.02-1.04)) and T2D were linear (1.09 (1.07-1.12)). Conclusions: Independent of PA, total sitting and TV viewing time are associated with greater risk for several major chronic disease outcomes. For all-cause and CVD mortality, a threshold of 6-8 h/day of total sitting and 3-4 h/day of TV viewing was identified, above which the risk is increased.